Determination of the Safe Orientation and Dip of a Rock Slope in an Open Pit Mine in Syria Using Kinematic Analysis - ZainAlabideen, Kinan; Helal, Maan (Nahrain University College of Engineering Journal, 2017)
This paper presents a method for choosing the orientation and the dip of an excavated rock slope, to safely serve the intended function of the slope or the excavation.The investigated slope is a rock slope in an open pit mine in Knifes, Syria.This mine is a phosphate mine. The phosphate is covered with the sedimentary organic limestone rocks, which are the subject of this research.The kinematic analysis method is adopted here to analyze the slope stability. This method uses stereographic projection principles and applies them in rock slope stability analysis. Open Stereo program of stereographic projection was used to obtain the required projections.A particular case study was performed in order to ensure that the studied part of the slope is safe, and a general case study was performed to present a suggested procedure for choosing safe dip and dip direction to the face of the studied slope.In this research, the results present the possible choices of the orientation and the dip of the excavated rock slope, to enlarge the open pitmine safely in future.Key Words: , .